ANALISIS PENEMPATAN DAN PENENTUAN JUMLAH TOWER CRANE (TC) - Syapril Janizar; Eko Rizky Suprapto (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2021)
In the construction of Cable Stayed Bridge, the use of heavy construction equipment is absolutely necessary, especially required for positioning and selecting the type of Tower Crane in order to improve construction performance. Therefore, human resources and heavy equipment used in the construction process will significantly affect the period of project implementation. Proper planning of the location for various construction equipment is believed to be the key of efficiency and productivity. Tower Crane as the target optimization is one of the equipment that has a big role in transporting the materials for the construction of a multi- storey building so that it requires proper planning to be able to serve all points of demand from its position.